Clarification of the type status of Macropsalis fabulosa Phillipps & Grimmett 1932 - Taylor, Christopher K. (Zootaxa, 2012)
The type status of Macropsalis fabulosa Phillipps & Grimmett 1932 was reviewed in Taylor (2011), under the current combination of Forsteropsalis fabulosa. As recorded therein, Forster (1944) designated a neotype for this species to replace the original, destroyed holotype. Unfortunately, Forster’s (1944) neotype was recognisably not a representative of the same species as the holotype illustrated by Phillipps & Grimmett (1932), but was identified by Taylor (2011) as a male of Forsteropsalis inconstans (Forster 1944) (described by Forster 1944 from the female only). Taylor (2011) stated that an application would be submitted to the ICZN in order to clarify the status of Macropsalis fabulosa by setting aside Forster’s neotype in favour of one that was conspecific with the lost holotype.